THE POLITICAL PROGRAMME OF THE GLOBAL JIHADIST MOVEMENT: BETWEEN DREAMS AND REALITY - Gailiūnas, Egidijus (Politologija, 2015)
This article deals with a phenomenon of the ‘global jihadist movement’. The article argues that the main goals that jihadists have in their political programme were not achieved. The only achievement that suits jihadists’ political programme is withdrawal of the US military forces from the Saudi Arabia in 2003. However, it is debatable whether this happened because of jihadists’ efforts. The main aim of the article is to find out how successful jihadists are in implementing their political programme. The article begins with a question: ‘What global jihadist movement is?’ At the beginning of the article the meaning of the global jihadist movement is analysed. The structure of the global jihadist movement is reviewed. The ‘Core al-Qaida’ and its place in the global jihadist movement are discussed. Further the article goes with a question: ‘What is the jihadist movement’s political programme?’ It is argued that the so-called jihadists’ political programme consists of ideological and strategic components. The specific jihadists’ vocabulary presented in the article is considered to be an important piece of movement’s ideology. The last part of the article is directly related to the article’s main aim. In this part the achievements related to implementation of the political programme of the global jihadist movement are analysed. The questions that are answered in the last part of the article: ‘How successful are jihadists in expelling Western forces from the Muslim countries in the Middle East?’, ‘How successful are jihadists in gaining power in the Muslim countries of the Middle East region?’, ‘How successful are jihadists in establishing the Caliphate governed under the Sharia law?’ In the article it is argued that jihadists are unable to realize their main goals from their political programme. Many ordinary Muslims see global jihadist movement’s goals as acceptable. However, they think that terrorist attacks, as the mean to achieve these goals, cannot be justified. For the future of the global jihadist movement three scenarios could be drawn. These are worst-case (jihadist movement will fail to achieve its goals) scenario, status quo scenario (jihadist movement will fail to achieve its goals, but continue to exist), and best-case scenario (jihadist movement will succeed in realizing all its goals). Which scenario will be the real one is difficult to say at the moment. Yet, it seems that the third one (best-case scenario) is least realistic, because after almost 10 years since 9–11 jihadists have had achieved none of their openly state goals.